Effects of dietary tussah immunoreactive substances on the growth performance, physiological response and serum metabolome of shrimp (Litopenaeus vannamei). (7th November 2021) - Wen, Zhixin; Li, Xuejun; Sun, Yongxin; Li, Yajie; Meng, Nan; Mi, Rui; Ma, Shuhui; Li, Shuying; Du, Xingfan
Abstract: Immune enhancers as the substitute of antibiotics for controlling the diseases and promoting animals' growth have been frequently used in the shrimp farming. In this study, two tussah immunoreactive substances (TIS) addition ratios (0.5% and 1.0%) in Litopenaeus vannamei culture were established and the effects of TIS on the growth performance, physiological responses and serum metabolome of L . vannamei were measured. Moreover, the resistance of L . vannamei to pathogenic bacteria after the TIS addition was evaluated. The results indicated that the improvement of growth performance was more effective with the higher addition rate of TIS. The higher weight gain rate induced by TIS addition could be due to the more powerful ability of lipid metabolism for producing more energy to promote the growth of L . vannamei . The increase in survival rate of L . vannamei could contribute by the higher serum immunity and disease resistance after the TIS addition for reducing the incidence of diseases. TIS addition also significantly changed the serum metabolome of L . vannamei, leading to the increases of vitamin B6 and vitamin E production, the improvement of environmental pressure resistance and the reduction of potential pathogen infection. The findings of this study showed the potential application of TIS in the shrimp farming, which could improve the growth performance and promote the lipid metabolism and immune capacity of shrimps.